History of Hypertension Is Associated With MR Hypoperfusion in Chinese Inpatients With DWI-Negative TIA - Wang, Yue; Liang, Huazheng; Luo, Yu; Zhou, Yuan; Jin, Lingjing; Wang, Shaoshi; Bi, Yong (Frontiers in Neurology, 2019)
Objectives: The present study aimed to examine the prevalence of and risk factors for magnetic resonance (MR) perfusion abnormality in a Chinese population with transient ischemic attack (TIA) and normal diffusion-weighted imaging (DWI) findings. Methods: Patients with TIA admitted to our stroke center between January 2015 and October 2017 were recruited to the present study. MRI, including both DWI and perfusion-weighted imaging (PWI) , was performed within 7 days of symptom onset. Time to maximum of the residue function (Tmax) maps were evaluated using the RAPID software (Ischemaview USA, Version 4.9) to determine hypoperfusion. Multivariate analysis was used to assess perfusion findings, clinical variables, medical history, cardio-metabolic, and the ABCD2 scores (age, blood pressure, clinical features, symptom duration and diabetes). Results: Fifty-nine patients met the inclusion criteria. The prevalence of MR perfusion Tmax  4 s  0 ml and  10 mL were 72.9% (43/59) and 42.4% (25/59), respectively. Multivariate analyses revealed that history of hypertension is an independent factor associated with MR perfusion abnormality (Tmax 4 s  10 mL) for Chinese patients with TIA (P=0.033, adjusted OR=4.11, 95%CI=1.12-15.11). Proximal artery stenosis (> 50%) tended to lead to a larger PW lesion on MRI (p=0.067, adjusted OR=3.60,95% CI =0.91-14.20). Conclusion: Our results suggest that the prevalence of perfusion abnormality is high as assessed by RAPID using the parametric Tmax  4 s. History of hypertension is a strong predictor of focal perfusion abnormality as calculated by RAPID on Tmax map of TIA patients with negative DWI findings.